CYBER COUNSELING BASED SELF COUNSELING IN OVERCOMING SUICIDE IDEATION IN ADOLESCENTS (Al-Tazkiah Jurnal Bimbingan dan Konseling Islam, 2023)
This study aims to determine the level of suicidal ideation in adolescents, the level of effectiveness of the use of self-counseling based on cyber counseling in overcoming suicidal ideation and data on the types of cyber counseling platforms and materials used in self-counseling by adolescents in overcoming suicidal ideation when facing severe psychological problems. This type of research is descriptive quantitative through a description of the level of suicidal ideation in adolescents. The research location was in the Islamic Education Guidance and Counseling (BKPI) study program, Faculty of Islamic Religion, University of Ibn Khaldun Bogor. The research population was all students in the BKPI study program who showed symptoms or indicators of suicidal ideation. The samples obtained were 84 students. The sampling technique used was purposive sampling. The data collection technique used a structured questionnaire containing an attitude scale related to suicidal ideation. Data analysis used the Quantitative Descriptive Analysis (QDA) technique. The results of data analysis on self-counseling research based on cyber counseling in overcoming adolescent suicide ideation in the Islamic Education Guidance and Counseling study program show that there are suicidal ideations in adolescents when facing acute or severe psychological problems. The dominant application of self-counseling based on cyber counseling helps adolescents to overcome suicidal ideation. The cyber counseling platforms used in the self-counseling process are YouTube, Instagram, WhatsApp, Twitter, Tik-Tok, Google, Telegram and Pinterest.